Investigating the Effects of Land Use Change on Subsurface, Surface, and Atmospheric Branches of the Hydrologic Cycle in Central Argentina. Issue 11 (8th November 2021) - Pal, Sujan; Dominguez, Francina; Bollatti, Pablo; Oncley, Steven P.; Yang, Yi; Alvarez, Javier; Garcia, Carlos M.
Abstract: Since the 1970s, land cover in central Argentina has shifted away from perennial crops and grasses toward annual crops, largely soy. In this study, we use observations and modeling to understand how this shift in land use has affected the sub‐surface, surface, and atmospheric fluxes of moisture and energy in a flat agricultural area. We analyze the flux tower data from a paired site at Marcos Juarez in central Argentina during the period of the RELAMPAGO field campaign (2018–2019). When compared to perennial alfalfa, the observations over soy show lower evapotranspiration (ET) and specific humidity, higher sensible heat, higher outgoing shortwave radiation, and soil temperature. Water table (WT) depth is shallower below the soy than the alfalfa sites. To better understand the long‐term temporal behavior from 1970s to present, the Budyko framework is used to show that the trends in ET cannot be explained by climate variables alone. We then use the Noah‐MP land surface model calibrated at both soy and alfalfa sites. Long‐term simulations of the calibrated model suggests that ∼95% of precipitation is evaporated in the alfalfa site with negligible recharge and runoff. Contrarily in the case of soy, ET is about 68% of precipitation, leaving nearly 28% for recharge and 4% for runoff. Observed increases in streamflow and decreases in WT depth over time are likely linked to shifts in land cover. Furthermore, the partitioning of net radiation shifts from latent heat to sensible heat resulting in a 250% increase in Bowen ratio (from 0.2 to 0.7). Key Points: RELAMPAGO field observations and Noah‐MP modeling are used to demonstrate that the fluxes of moisture and energy differ significantly between alfalfa and soy crops in central Argentina Water table depth has significantly decreased, and runoff has increased over agricultural areas of central Argentina during the recent decades Land cover changes partly explain regional changes in water table depth, runoff, and Bowen ratio in central Argentina